THE SOCIAL AND ETHICAL THOUGHT OF THE BOGOMILLS (Annual of the Faculty of Philosophy in Skopje, 2023)
The history of the Macedonian people is really rich with, above all, giant figures. The article is dedicated to one such giant - priest Bogomil, to the spiritual source and inspiration of ethics in/among the Bogomils. It is a philosophy that appears as a new anthropological turn in philosophical knowledge, after the Socrates one. Namely, man is once again the centre of creation and from his moral choice as the choice of a man - a citizen, and not of a subject or a nameless member of the respective church community depends on the vigilance of the Universe, as well as the existing social order. At the same time, the idea is to give also an additional and sustained contribution to the study and affirmation of the social-ethical thought and action of the Bogomils, very essential, but forgotten, for our national essence.
Keywords: bogomilism; ethics; national essence; church; humanism; responsibility